Should We Be Worried About Income Inequality in Ireland? - LAYTE, RICHARD (ESRI, 2011)
Despite the recession Ireland remains a country with relatively high income inequality. Ireland sits just behind the UK near the top of the inequality rankings in Europe behind the Baltic and Southern European states. Is this a problem? Should we be concerned about levels of income inequality in Irish society? Debates about this issue often centre on the moral acceptability of income inequality with protagonists adopting well worn ideological positions but is there actually any evidence that higher levels of income inequality are a problem? Some may have moral misgivings about excessively high incomes at the top and those at the bottom being left behind as middle incomes increase, but does inequality in itself, as opposed to being poor, actually have any consequences? Recent ESRI research suggests that the answer is yes.
PUBLISHED
Dublin
ESRI Research Bulletin 2011/02/03
Keywords: Economics; Ireland; income inequality